STRATEGI PENGEMBANGAN LEMBAGA KEUANGAN MIKRO SYARIAH DI INDONESIA: PENDEKATAN MATRIKS IFAS EFAS - Rusydiana, Aam S; Firmansyah, Irman (Universitas Muhammadiyah Prof DR HAMKA, 2018)
LKMS is a financial institution that is oriented towards improving the welfare of members and society. Despite growing rapidly, LKMS is still experiencing many obstacles in its development. There are still many problems faced by this institution both from the internal and external side. This study attempts to identify the causes and factors that are dominantly an obstacle to the development of LKMS in Indonesia, using IFAS EFAS Matrix and SWOT approaches, along with the solutions offered. Based on the IFE analysis that the highest rating of the power of small and medium enterprises (MSMEs) is followed by high local initiative. While the weakness rating is the cost of human resource training and entrepreneurship training followed by the cost of licensing. The results of EFE analysis that the highest ranking of the opportunities that are financed sector is very flexible followed by the public interest factor toward sharia transaction is getting bigger. While the highest ranking of threats is competition followed by weak regulation and legality LKMS. It is expected that there will be a joint commitment from various parties either from policymakers or academics and practitioners in supporting and encouraging the development effort of sharia finance industry, especially in this case LKMS.